OPTIMAL INTEGRATION OF DISTRIBUTION SYSTEM OF DG UNITS BASED ON WIND GENERATOR WITH CONSIDERATION OF UNCERTAINTIES (Academia Science Repository, 2023)
Global environmental problems associated with traditional energy generation have led to a rapid increase in the use of renewable energy sources (RES) in power systems. The integration of renewable energy technologies is commercially available nowadays, and the most common of such RES technology is wind turbine (WT). This paper proposes an application of Salp Swarm Algorithm (SSA) for determining the optimal allocation of WT based distributed generation (DG) units in the distribution system (DS) with the aim of minimizing the total power and energy losses.